The crystal structure of 4-(4-phenyl-5-(((1-(2,4,6-tribromophenyl)-1H-1,2,3-triazol-4-yl)methyl)thio)-4H-1,2,4-triazol-3-yl)pyridine, C22H14Br3N7S - Al-Sa’doni Haitham; El-Naggar Mohamed; Shehadi Ihsan A.; Hasan Kamrul; Khanfar Monther A. (Zeitschrift für Kristallographie - New Crystal Structures)
C22H14Br3N7S, H2O, triclinic, P 1‾ $\overline{1}$ (no. 2), a = 8.9098(17) Å, b = 9.422(2) Å, c = 15.702(4) Å, α = 86.453(9)°, β = 78.382(7)°, γ = 69.477(7)°, V = 1209.1(5) Å3, Z = 2, Rgt (F) = 0.0315, wRref (F 2) = 0.0802, T = 100(2) K.